Therapeutic Perspectives for the Perioperative Period in Oral Squamous Cell Carcinoma (OSCC) - Galmiche, Antoine; Saidak, Zuzana; Bettoni, Jérémie; Ouendo, Martial; Testelin, Sylvie (Frontiers in Oral Health, 2022)
The perioperative period is the relatively short window of time, usually measured in days or weeks, around the surgical procedure. Despite its short duration, this time period is of great importance for cancer patients. From a biological point of view, the perioperative period is complex. Synchronous with primary tumor removal, surgery has local and distant consequences, including systemic and local inflammation, coagulation and sympathetic activation. Furthermore, the patients often present comorbidities and receive several medical prescriptions (hypnotics, pain killers, anti-emetics, hemostatics, inotropes, antibiotics). Because of the complex nature of the perioperative period, it is often difficult to predict the oncological outcome of tumor resection. Here, we review the biological consequences of surgery of Oral Squamous Cell Carcinoma (OSCC), the most frequent form of primary head and neck tumors. We briefly address the specificities and the challenges of the surgical care of these tumors and highlight the biological and clinical studies that offer insight into the perioperative period. The recent trials examining neoadjuvant immunotherapy for OSCC illustrate the therapeutic opportunities offered by the perioperative period.